Royal Mail Steamship Titanic - Hamilton, Sue L., 1959- (Bloomington, Minn. : Abdo & Daughters ; Minneapolis, Minn. : Rockbottom Books [distributor], 1988)
A ship officer's account of the Titanic's last hours.
A fictional account based on factual data.
Spine title: R.M.S. Titanic.
Includes bibliograhical references (p. 32).
Keywords: Titanic (Steamship) -- Juvenile fiction; Shipwrecks -- North Atlantic Ocean -- Juvenile fiction